A triple WAP domain containing protein acts in antibacterial immunity of weather loach, Misgurnus anguillicaudatus. Issue 103 (August 2020) - Zhang, Xiao-Wen; Yang, Cong-Hui; Xia, Xiao-Hua; Pan, Xin-Tong; Jin, Ze-Yu; Yu, Hao; Zhang, Hong-Wei
Abstract: Whey acidic protein domain (WAPD) occurs in a variety of proteins in animals and many of WAPD-containing proteins are involved in immunity. In the present study, a novel protein containing three WAPDs was identified from the weather loach, Misgurnus anguillicaudatus, designated as Ma TWD. Ma TWD share high identity with TWDs from fish but low identity with TWDs from other animal phyla. MaTWD transcripts mainly distributed in gills and head kidney responded to bacterial challenge with significant upregulation. In vitro assay with recombinant Ma TWD protein revealed that Ma TWD had antiprotease activity against bacterial proteases. Moreover, Ma TWD exhibited bacterial binding capacity and antimicrobial activity. Most importantly, exogenous Ma TWD protected loach against bacterial infection by reducing loach mortality. We infer that Ma TWD participates in the antibacterial immunity of loach via its antiprotease and antimicrobial activities. Highlights: A protein with three whey acidic protein domains (WAPDs) in tandem is identified from weather loach. MaTWD exhibits antiprotease, antimicrobial and bacterial binding activities. MaTWD protects loach against bacterial infection. First functional study of such a WAPD protein in fish.